Flypaper Effect Pada Pendapatan Asli Daerah (PAD) dan Dana Alokasi Umum (DAU) Terhadap Belanja Daerah (Studi Pada Pemerintahan Kabupaten/Kota di Provinsi Jawa Timur, Jawa Tengah dan Jawa Barat Periode 2011-2013): Flypaper Effect on Regional Original Income (PAD) and General Allocation Funds (DAU) on Regional Expenditures (Study on District/City Governments in East Java, Central Java and West Java for the Period 2011-2013) - Suryani, Ade Irma (Universitas Muhammadiyah Sidoarjo, 2018)
This study aims to determine the effect of local revenue (PAD) and the General Allocation Fund (DAU) to the Expenditures of Regional as well as the possibility of flypaper effect on the country/city in East Java, Central Java and West Java the period 2011-2013. The method used in thus research is quantitative method. The population used is the district/city in East Java, Central and West Java. Sampling using purposive sampling and sample in this research is 100 district/cities with details of East Java Province 38 District/city, West Java 35 district/city and West Java 27 district/city.The data used in this research is secondary data which the data obtained from reports of Regional Budget obtained via the website Ministry of Finance of the Republic of Indonesia Directorate General of Regional Financial Balance. The analysis in this research is using descriptive analysis, classical assumption test and multiple linear regression. Result from this research that indicates that the local revenue (PAD) affects regional expenditure as well as with the General Allocation Fund (DAU) also affects regional expenditure and occurred flypaper effect on the country/city in East Java,Central Java and West Java periods 2011-2013.